2022
DOI: 10.3390/app122413033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Cooling Performance of a Hybrid Microchannel and Jet Impingement Heat Sink

Abstract: Thermal management at a high heat flux is crucial for high-power electronic devices, and jet impingement cooling is a promising solution. In this paper, a hybrid heat sink combining a microchannel and jet impingement was designed, fabricated and tested in a closed-loop system with R134a as the working fluid. The thermal contact resistance was measured by using the steady-state method, and the thermal resistance of the heat sink was obtained at different heat fluxes and flow rates. The maximum heat dissipation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Xiao et al [30] designed, manufactured, and tested a closed-loop system combining a microchannel sink and jet impingement with R-134a as the working fluid. The study concluded that the hybrid heat sink can be used to achieve low thermal resistance, stemming from a highly dense micro-jet array with separate inflow and outflow microchannels.…”
Section: Optimization Of Mchsmentioning
confidence: 99%
“…Xiao et al [30] designed, manufactured, and tested a closed-loop system combining a microchannel sink and jet impingement with R-134a as the working fluid. The study concluded that the hybrid heat sink can be used to achieve low thermal resistance, stemming from a highly dense micro-jet array with separate inflow and outflow microchannels.…”
Section: Optimization Of Mchsmentioning
confidence: 99%
“…Since the end of the 20th century, Choi et al [6] proposed the concept of "nanofluid" for the first time, it has gradually received extensive attention from the heat transfer community [16]. In recent years, researchers have conducted a large number of experiments and in-depth studies on nanofluid flow heat transfer, mainly focusing on the application of nanofluids to microchannel enhanced heat transfer [7].Tan et al [8] compared single-jet and multi-jet microchannel heat sinks by discussing the temperature profiles, pressure drop, and heat transfer characteristics of the arrangement of the jet channels, and the results showed that the integration of the jet impingement further improves the thermo-hydrodynamic properties of the MCHS.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years jet impingement cooling technology has gradually become a research hotspot in the field of thermal management of high power micro-scale electronic components due to its ability to effectively remove the heat generated by the operation of microelectrical appliances and thus prolonging the service life of electronic devices [10][11][12][13][14][15][16][17][18].Pandey et al [19] investigated the enhanced cooling performance of a hybrid micro-channel radiator consisting of micro-channels, nozzles, and struts in terms of various hydrothermal characteristic parameters and analyzed the effects of parameters including jet inclination angle, Reynolds number, and convective heat transfer. performance and analyzed the effect of parameters including jet inclination angle, Reynolds number and nozzle diameter on convective heat transfer, and found that reducing the nozzle diameter reduces the wall temperature and pressure drop, which results in better cooling effect.Peng et al [20] carried out numerical simulations of multi-jet microchannels to compare and analyze the effect of various geometrical parameters on jet microchannels, and found that the number of jets is higher, the outlet is wider, the fin width It was found that the jet microchannel with a larger number of jets, a wider outlet, and a smaller fin width compared with the channel width has a better cooling performance.…”
Section: Introductionmentioning
confidence: 99%